Implementation of the PBLHS Movement Through Reducing Single-Use Plastic Waste at Al-Fatah Middle School - Naryatmojo, Deby Luriawati; Kusumantoro, Kusumantoro; Khatamy, Muhammad Adam (Universitas Negeri Semarang, 2025)
This community service activity aims to enhance the capacity of school members in implementing the Environmental Care and Culture Movement in Schools (GPBLHS) at SMP Al-Fatah Terboyo, Semarang City. The program was motivated by low environmental awareness and the high amount of single-use plastic waste within the school environment. The methods included training for teachers on integrating environmental themes into the curriculum, socialization of plastic waste reduction, and facilitation of reusable tumbler use among school members. Evaluation was conducted through pre- and post-tests to measure behavioral changes and waste reduction. The results indicated improved teacher competence in developing environmentally themed lesson plans and a decrease in inorganic waste volume from 30.9 kg to 3.8 kg after the program. This activity demonstrates that environmental education through curriculum integration and behavioral facilitation effectively supports Adiwiyata school initiatives toward sustainable and environmentally conscious schools.